Imaging of Bone Metastases in Breast Cancer - Cook, Gary J.R. (Semin Nucl Med, 2022)
Bone metastases are a common site of spread in advanced breast cancer and responsible for morbidity and high health care costs. Imaging contributes to staging and response assessment of the skeleton and has been instrumental in guiding patient management for several decades. Historically this has been with radiographs, computed tomography and bone scans. More recently, molecular and hybrid imaging methods have undergone significant development, including the addition of single photon emission computed tomography/computed tomography to the bone scan, positron emission tomography, with bone-specific and tumor-specific tracers, and magnetic resonance imaging with complementary functional diffusion-weighted imaging. These have allowed different aspects of the abnormal biology associated with bone metastases to be explored. There is ability to interrogate the bone microenvironment with bone-specific tracers and cancer cell characteristics with tumor-specific methods that complement morphological appearances on computed tomography or magnetic resonance imaging. Alongside the advent of novel, more effective and nuanced therapies for bone metastases in breast cancer, there is accumulating evidence that the developments in imaging allow more sensitive and specific detection of bone metastases as well as more accurate and earlier assessment of treatment response leading to improvements in patient management.